The future of philology: proceedings of the 11th Annual Columbia University German Graduate Student Conference - Bajohr, Hannes (Cambridge Scholars Publishing, 2014)
Philology, master science of the nineteenth century, has changed so radically over the course of the twentieth century that it is hardly recognizable in the twenty-first. Its scope has been transformed, its methodology contested, and its legitimacy called into doubt. Does it still make sense to speak institutionally and epistemologically of 'philology'? Does this venerable title continue to signify a truly coherent field, and not a multitude of scattered currents and competing genealogies
The many lives of Dasein:Towards a philological a pproach to the Heideggerian corpus by digital means contributors. - Includes bibliographical references at the end of each chapters
Keywords: Konferenzschrift -- 2012 -- New York, NY; Konferenzschrift -- 2014 -- New York, NY; Germanistik; Historische Sprachwissenschaft; Philologie